Non-enzymatic Amperometric Sensor for H2O2 Based on MnCO3 Thin Film Electrodes - Stojkovikj, Sasho; Najdoski, Metodija; Sefer, Birhan; Mirceski, Valentin (Croatica Chemica Acta, 2018)
The present study describes development of a non-enzymatic amperometric sensor for detection of H2O2 based on MnCO3 thin film electrodes. The film was deposited on electroconductive FTO coated glass substrates using simple chemical bath deposition method. The phase composition of the thin film was confirmed by X-ray diffraction analysis. The electrochemical properties and the sensor sensitivity towards H2O2 were examined using cyclic voltammetry and chronoamperometry in 0.1 M phosphate buffer solution with pH = 7.5. It was revealed that the sensing mechanism is based on electrocatalytic oxidation of H2O2, involving Mn species as redox mediators. According to the results, the best sensor response towards H2O2 was found at E = +0.25 V, with detection limit and sensor sensitivity of 10.0 mu M and 2.64 mu A cm(-2) mM(-1) (for the range of 0.09-1.8 mM), respectively, associated with R-2 = 0.999.
CRIS-Team WoS Importer:2019-04-12